Expression of GFP-fusions in Arabidopsis companion cells reveals non-specific protein trafficking into sieve elements and identifies a novel post-phloem domain in roots. - Stadler, Ruth; Wright, Kathryn M.; Lauterbach, Christian; Amon, Gabi; Gahrtz, Manfred; Feuerstein, Andrea; Oparka, Karl J.; Sauer, Norbert (Plant Journal, 2005)
Transgenic Arabidopsis plants were constructed to express a range of GFP-fusion proteins (36-67 kDa) under the companion cell (CC)-specific AtSUC2 promoter. These plants were used to monitor the trafficking of these GFP-fusion proteins from the CCs into the sieve elements (SEs) and their subsequent translocation within and out of the phloem. The results revealed a large size exclusion limit (SEL) (>67 kDa) for the plasmodesmata connecting SEs and CCs in the loading phloem. Membrane-anchored GFP-fusions and a GFP variant targeted to the endoplasmic reticulum (ER) remained inside the CCs and were used as 'zero trafficking' controls. In contrast, free GFP and all soluble GFP-fusions, moved from the CCs into the SEs and were subsequently translocated through the phloem. Phloem unloading and post-phloem transport of these mobile GFP-fusions were studied in root tips, where post-phloem transport occurred only for the free form of GFP. All of the other soluble GFP-fusion variants were unloaded and restricted to a narrow zone of cells immediately adjacent to the mature protophloem. It appears that this domain of cells, which has a peripheral SEL of about 27-36 kDa, allows protein exchange between protophloem SEs and surrounding cells, but restricts general access of large proteins into the root tip. The presented data provide additional information on phloem development in Arabidopsis in relation to the formation of symplasmic domains.